FBG AND TC/HDL RATIOS IN TYPE 2 DIABETES MELLITUS - HANIF, RUHILA; SATTAR, ABDUS; QAYUM, IFTIKHAR (Journal of Ayub Medical College Abbottabad, 2001)
Background: Presence of dyslipidemia. i.e. raised Total Cholesterol (TC) and decreased High Density Lipoproteins (HDL) is an established phenomenon in type 2 diabetes mellitus. Its relationship to the fasting blood sugar (FBG) level in both diabetics and non-diabetics has yet to be established. The present study aims to show such a relationship. Methods: 150 subjects were selected and divided into two groups, one of 50 controls (non-diabetics), the other of 100 patients with type 2 diabetes mellitus. Their FBG levels were determined by enzyme oxidase method, and their TC and HDL levels were determined using a standard kit method. Results: FBG and TC: HDL ratios were increased in the patient group (p = <0.001). Comparison of FBG and TC: HDL ratios revealed a highly significant rise (p = <0.001) in the patient group. FBG with TC: HDL ratios between both groups showed a positive correlation (r = 0.554). Conclusion: The results of the present study suggest an association between FBG and TC: HDL ratios, which may be a contributory factor to the increased prevalence of coronary artery disease in patients with type 2 diabetes mellitus.